Character strategy: exploring character strengths using real-life story model’s as positive therapy intervention in college - Nurfarhanah Nurfarhanah; Mudjiran Mudjiran; Neviyarni Suhaili; Daharnis Daharnis (Journal of Educational and Learning Studies, 2022)
Character as an important result of education seeks so that individuals can understand and behave properly in accordance with moral values in their lives. The character building strategy has been implemented even applied in several researches and studies in universities. One effort to build the right character is done for students through the implementation of ongoing guidance of character values and manifested in behavior. The Real-Life Story (RELIST) model as one of the positive therapeutic interventions is felt to be more appropriately applied also in developing individual character identification of character strengths related to the development of individual strengths or strengths, through a series of structured and systematic activities.